2018
DOI: 10.1080/00268976.2018.1484950
|View full text |Cite
|
Sign up to set email alerts
|

Nanorings in planar confinement: the role of repulsive surfaces on the formation of lacuna smectics

Abstract: We study the structure and liquid-crystalline phase behaviour of a model of confined non-convex circular soft-repulsive nanorings in a planar slit geometry using molecular-dynamics simulation. The separation distance between the structureless parallel soft-repulsive walls is made large enough to allow for the formation of a distinct bulk phase in the central region of the box which is in coexistence with the adsorbed fluid thus allowing the analysis of single-wall effects. As the density of the particles is in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 90 publications
1
10
0
Order By: Relevance
“…Avendaño et al . 15 simulated soft-repulsive rings between parallel, soft-repulsive walls, with results that are in stark contrast to the behavior of convex DLCs. Finally, other numerical studies of confined DLCs have employed the popular Gay–Berne (GB) model and more complex wall–particle interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Avendaño et al . 15 simulated soft-repulsive rings between parallel, soft-repulsive walls, with results that are in stark contrast to the behavior of convex DLCs. Finally, other numerical studies of confined DLCs have employed the popular Gay–Berne (GB) model and more complex wall–particle interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Hard walls were revealed to induce homeotropic (face-on) anchoring and stabilise the N phase, whereas adsorbent walls promoted planar (edge-on) alignment and a more disordered bulk. Avendaño et al [20] have reported what is, to our knowledge, the only computer simulation of a non-convex DLC composed of softrepulsive rings between parallel, soft-repulsive walls. These tend to align edge-on, forming low-density smectic layers with anti-nematic order and no biaxiality, in stark contrast to the behaviour of convex DLCs.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23][24][25][26] Self-assembly of particles with non-convex shapes has also been used for the design and fabrication of highly open structures as in most cases their shapes, even at their most efficient possible packing attained, hinder the formation of closed-packed structures. [27][28][29] For example, ring-shaped [30][31][32][33][34][35] wireframe, 36 and branched particles [37][38][39][40] exhibit the formation of three-and quasi-two-dimensional highly open porous structures when the particle geometry is highly non-convex. Examples of non-convex particles confined in 2D have also been studied experimentally and in simulations.…”
Section: Introductionmentioning
confidence: 99%